Pengaruh Metode Bernyanyi terhadap Kemampuan Mengenal Huruf pada Siswa Kelas I SD Negeri I Kalisapu Kabupaten Cirebon - Rokhmatun Nabillah; Niken Anis Maghfiroh; Abdul Sholeh (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama'ah, 2025)
This research was motivated by the conventional learning methods still commonly used in Grade I classrooms, with limited variation in instructional approaches. As a result, students experience difficulties in recognizing letters, such as distinguishing letter shapes, naming letters, and associating them with sounds. One strategy to improve letter recognition skills is through the implementation of singing as a teaching method. The objective of this study was to examine the effect of the singing method on letter recognition skills among first-grade students at SD Negeri 1 Kalisapu. This research employed a quasi-experimental method with a quantitative approach, using a non-equivalent control group design. The population of the study consisted of all students at SD Negeri 1 Kalisapu, with the sample being all 36 first-grade students. The results of the Independent Sample t-test showed a significance value of 0.01 (0.01 < 0.05), indicating that the singing method had a significant effect on students' letter recognition abilities. The N-Gain test results showed an average N-Gain score of 0.4967 in the experimental group, which is greater than 0.3, falling into the ‘moderate’ category. This suggests that the application of the singing method was moderately effective in improving students' letter recognition skills. These findings demonstrate that the implementation of the singing method has a significant impact on the letter recognition abilities of Grade I students at SD Negeri 1 Kalisapu.